The effect of human resource practices on organizational citizenship behavior - Noor Azlina, Che Daud (2013)
Many researchers conducted study in the area of organizational citizenship behaviour but there is little research and less focus on service organizations, particularly educational institution. The study is a replication of Veldhoven and Meijman (1996), Johnson (1996), Lytle, Hom and Mokwa (1998), Weer (2006), Podsakoff and Mckenzie (1994) which adapting 25 item instruments on participation in decision making, training and development and career development that will impact on the exhibition of organizational citizenship behaviour among administrative staff in the university. The study aims to understand the relationship of human resource practices on organizational citizenship behaviour within the context of university as educational institution. Based on the analysis it was found that career management and training made significant contributions to organizational citizenship behaviour. Recommendations and implications for future research and practice were also discussed